THE EFFECT OF USING CODE MIXING TECHNIQUE ON STUDENTS’ SPEAKING ABILITY OF TENTH GRADE STUDENTS OF SMK SWASTA TUNAS PELITA BINJAI - Nudia Yultisa; Mhd. Yusuf Aziz; Ihsani Diah Anjariah (PT. Radja Intercontinental Publishing, 2020)
This study deals with the effect of code mixing technique on students’ speaking ability. The objective of this study was to find out if there was a significant effect of code mixing technique on students’ speaking ability. It was conducted by using experimental research. The population of this study was the tenth grade students of SMA Tunas Pelita Binjai which consists of two classes. Two classes were taken as the sample of this research, X-I and X-2. The class of X-1 was an experimental group and X-2 was a control group. The experimental group was taught by code mixing technique, otherwise the control group was taught by using conventional method. The instrument for collecting the data was speaking task. The data were analyzed by using t-test formula. The result that was gained from the research proved the effect between students’ score in learning speaking English by using Code Mixing technique and without using code mixing. According to statistical calculations, sig. (2-tailed) and with df 50 in significance level 5% t-table = 1.676 with p-value = 0.010 and α = 0.05. which is, p-value < α. It means that to >t-table. Therefore, it proved that the Null Hypothesis (Ho) is rejected and the Alternative Hypothesis (Ha) is accepted. Therefore, it can be concluded that Code Mixing technique is effective on teaching speaking English because it showed a significant effect on students’ speaking ability in tenth grade of SMK Tunas Pelita Binjai with the scale of moderate significant.